THE IMPACT OF THE NATIONAL ECONOMIC RECOVERY PROGRAMME IMPLEMENTATION ON INDONESIA GROSS DOMESTIC PRODUCT GROWTH - Ario Seno Nugroho; Sessa Tiara Maretaniandini (Program Sarjana Manajemen Universitas Internasional Batam, 2023)
Covid-19 Pandemic strikes almost all the economies in the world. The World Economy plumes out and grows negatively. Each country tries to cope with this problem by introducing several policies, such as lockdowns and economic aid. This paper tries to study the impact of the Indonesia policy to resolve the economy (Economic Recovery Program) to the Gross Domestic Product (GDP) Growth. Using Eviews application to create ARIMA model, this study forecasts Indonesia's GDP Growth without an economic recovery program. In addition, this paper compares the condition between GDP Growth with and without economic recovery policy. The result shows GDP Growth is higher when there is an economic recovery program compared to GDP Growth (prediction) without the recovery policy.